2005
DOI: 10.1128/cdli.12.10.1231-1234.2005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of LIAISON Treponema Screen, a Novel Recombinant Antigen-Based Chemiluminescence Immunoassay for Laboratory Diagnosis of Syphilis

Abstract: The purpose of this study was to evaluate the diagnostic performance of LIAISON Treponema Screen (DiaSorin, Saluggia, Italy), a new automated chemiluminescence immunoassay (CLIA), in comparison with that of rapid plasma reagin (RPR) and the following currently used treponemal tests: hemagglutination test (TPHA), immunoenzymatic assay (EIA), and Western blot (WB). First, a retrospective study was performed with a panel of 2,494 blood donor sera, a panel of 131 clinical and serologically characterized syphilitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 19 publications
(17 reference statements)
3
39
0
8
Order By: Relevance
“…Several different immunoassays set up with whole-cell lysate (12)(13)(14)(15) or recombinant T. pallidum antigens (16)(17)(18)(19)(20)(21)(22) are described in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different immunoassays set up with whole-cell lysate (12)(13)(14)(15) or recombinant T. pallidum antigens (16)(17)(18)(19)(20)(21)(22) are described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Treponemal tests include the serum fluorescent treponemal antibody absorption test, the T. pallidum hemagglutination test (TPHA) (Radim, Pomezia, Italy), the enzyme-linked immunoassay (ELISA), and the Western Blot (WB) assay; both ELISA and WB tests can be based on either whole-cell lysate (12)(13)(14)(15) or recombinant (16)(17)(18)(19)(20) treponemal antigens. More recently, chemiluminescent immunoassays set up with recombinant antigens have been evaluated (21,22). The purpose of this study was to evaluate the diagnostic performances of Enzygnost Syphilis (Dade Behring, Marburg, Germany) in comparison with ARCHITECT Syphilis TP (Abbott Japan Co., Tokyo, Japan).…”
Section: Introductionmentioning
confidence: 99%
“…Specificity was 99.9% for all treponemal tests. From 96 sera obtained from patient suffering from potentially cross-reactive conditions, no serum gave a positive result by LIAISON (Marangoni et al, 2005). However, another study for evaluation of LIAISON test found lower sensitivity of 94.1% (48/51), in primary and secondary syphilis (Knight et al, 2007).…”
Section: Immunochemoluminescence Assay (Cia) and Multiplex Flow Immunmentioning
confidence: 99%
“…The sensitivities of these commercial assays ranged from 23 to 77%, compared to 44% for VDRL (15). Marangoni et al reported CLIA and EIA sensitivities of 100 and 57%, respectively, for primary syphilis (11). With regard to secondary, latent, and late syphilis, most studies show superior sensitivity of treponemal immunoassays over nontreponemal assays.…”
mentioning
confidence: 99%
“…Among primary cases, the sensitivities of nine EIAs ranged from 93 to 98%, while the sensitivity of one kit was 88%. Marangoni et al evaluated the performance of commercial CLIA and EIA kits (11). Among 54 cases of untreated syphilis, the sensitivities of CLIA, EIA, and RPR were 100, 94, and 96%, respectively.…”
mentioning
confidence: 99%